Honey and Service - Leitch, Joan (Auckland University of Technology, 2023)
This work comprises a creative element, Honey and Service, and a critical work, Miss Bumby’s Mission. Honey and Service is a historical novel about New Zealand’s first beekeeper, Miss Mary Anna Bumby, who left England by sailing ship and arrived in the Hokianga in 1839 with two hives of honey bees. The novel explores her motivations and experiences on her journey and during her first four years in New Zealand. It highlights the difficulties of travelling with bees and working them in a new country with methods which were current then, but are now no longer used. Miss Bumby’s Mission is the critical component of the work. It investigates the author’s motivation for writing this story, how the extensive research was undertaken, and decisions which were made on how to present the material. It discusses the responsibilities and difficulties which come from writing about a real person from the past in the form of a biographical novel